Hydration properties of soybean protein isolates - Remondetto, G. (2001)
Hydration properties of soybean isolates with different processing conditions (heat treatments, pH and protein concentrations) were studied. Degree of denaturation, solubility in water, in 0.2mol/L NaCl, and in media of different sodium dodecyl sulfate concentrations, viscosity and water imbibing capacity of the different samples were determinated and correlated. Treatments at temperatures higher than 80°C denatured US and 7S proteins, leading to exposure of'Hydrophobie groups, which produced insoluble aggregates either in water or in high ionic strength media. These isolates possessed high water imbibing capacities and gave rise to viscous dispersions. Significant correlations were obtained between hydration properties and the "m" coefficient as calculated by a power law equation relating viscosity with the protein concentration of the dispersion. This "m" coefficient also correlated with the denaturation enthalpy of the protein isolates. On the basis of these results, it might be suggested that the "m" coefficient - dependent of the hydrodynamic behaviour of the particles - was a good estimator of the degree of protein denaturation.